Strategi Pembelajaran Inkuiri terhadap Hasil Belajar IPS Siswa Madrasah Ibtidaiyyah - Evarianisa Endang Trisnani (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2024)
This study aims to examine the effect of the inquiry-based learning strategy on students’ learning outcomes in Social Studies (IPS) at Madrasah Ibtidaiyah (MI). Social Studies education at the elementary Islamic level plays a vital role in shaping students’ social awareness, Islamic values, and critical thinking skills. However, conventional teacher-centered teaching methods often result in passive learning and a superficial understanding of the material. The inquiry-based strategy offers an alternative approach that promotes active student engagement through questioning, investigating, analyzing, and drawing conclusions independently or collaboratively. This research employed a quantitative approach with a quasi-experimental method involving two groups of fifth-grade MI students: an experimental group taught using the inquiry strategy and a control group taught using conventional methods. Data were collected through learning outcome tests, observation, and documentation, and analyzed using a t-test. The findings revealed that the application of inquiry-based learning significantly improved students’ Social Studies achievement. Students demonstrated increased engagement, curiosity, and a deeper understanding of the subject through the systematic inquiry process. Therefore, this strategy is recommended for broader implementation in Social Studies learning at MI to foster more meaningful, student-centered, and higher-order thinking-based education.